A Framework for Customer Engagement Behaviour in the Financial Services Industry : A Critical Review of Evidence - Kini, Archana Nayak; Basri, Savitha (Indian Journal of Finance, 2022)
In the post-COVID era, while the use of technology-enabled contactless financial services is growing, it is more critical than ever to match the rising customer expectations by aiding customers in making the best decisions and fulfilling their aspirations. The paper’s objective was to critically review published research on the antecedents of non-transactional customer engagement behaviors (CEBs), such as relationship quality, emotions, customer empowerment, and the influence of the CEBs on customer loyalty and advocacy in the financial services industry. Relevant online databases were comprehensively searched through Boolean search, reviewed critically, and synthesized narratively. The guidelines of PICO (participants, interventions, comparisons, outcomes) were followed. The final results indicated that an empowered, satisfied, highly pre-dispositional customer possessing different affective states and trust reciprocated positive engagement behaviors (CEBs). The positive CEBs build attitudinal loyalty and advocacy behaviors that create value in the long term. This review guided on managing customer tendencies to positively and emotionally engage with the product and brand in many ways, such as reviews and testimonials, to curtail switch-over behaviors, encourage customer advocacy, and loyalty behaviors.